Does a natural killer need a CAR? - Wang, Kangbo; Zhang, Yumo; Han, Zhibo; Wang, Youwei (Frontiers in Immunology, 2025)
Chimeric antigen receptor T cell (CAR-T) therapy has revolutionized cancer immunotherapy by overcoming intrinsic limitations in T cell activation, achieving remarkable success in treating relapsed or refractory hematologic malignancies in both pediatric and adult populations. Inspired by this success, researchers have turned their attention to natural killer (NK) cells—innate lymphocytes capable of recognizing and killing tumor cells without prior sensitization—and have begun designing CARs specifically adapted to NK cell biology. Unlike T cells, NK cells possess intrinsic cytotoxicity that does not solely rely on CAR-mediated activation. Moreover, NK cell-mediated antitumor responses can often be enhanced by simply increasing NK cell numbers, a strategy less effective in T cell-based therapies due to the complex mechanisms of tumor immune escape. This review explores the principles and strategies behind NK-adapted CAR design, critically examines whether CARs are essential for NK cell function, and discusses the opportunities and challenges in translating CAR-NK therapy into clinical practice.